Clinical consequences of untreated dental caries in youth population using pulpal involvement, ulceration, fistula, and abscess index - Kharel, Smriti; Dixit, Punam Basnet; Shrestha, Deepti; Ghimire, Siddharth; Dahal, Sirjana; Dhakal, Samikshya (Journal of Kathmandu Medical College, 2023)
Background: Dental caries is a major health problem worldwide despite improvements in oral health. It is one of the leading causes for extraction of teeth. Untreated caries may lead to pain and infection causing negative impact on a patient's personal well-being. Implementation of preventive strategies is the most cost-effective measure to prevent dental caries and its consequences. Objectives: To find out the consequences of untreated dental caries in the youth population using pulpal involvement, ulceration, fistula, abscess index. Methods: A descriptive cross-sectional study was carried out in 295 patients aged 15 to 24 years visiting the Department of Conservative Dentistry and Endodontics at Kathmandu Medical College with a complaint of dental caries from October 2021 to February 2023 after obtaining ethical approval. The data obtained were entered and analysed using Statistical Package for Social Sciences. Mean, median, standard deviation, frequency and percentage were calculated depending upon the nature of data. Results: Among various consequences of untreated dental caries, pulpal involvement was the most common consequences followed by abscess. Pupal involvement was found in 57 (19.32%) individuals and abscess in two (0.68%) individuals. None of the participants presented with ulceration and fistula. There was no significant association seen between age and sex with presence of pulpal involvement, ulceration, fistula and abscess among the individuals examined. Conclusion: Dental caries is a global issue that affects many people. It is possible to reduce the prevalence of caries and mitigate its associated consequences by increasing awareness and implementing preventive strategies on a national level.